Silicon self-assembled growth of quantum dots grown on corning glass (7059) substrate - Sakrani, Samsudi; Lim, Qiao Jie; Sumpono, Imam (Ibnu Sina Institute for Fundamental Science Studies, 2007)

(untitled)
Silicon quantum dots have been grown on corning glass(7059) substrate using a self-assembly method of physical vapour deposition. The samples were fabricated at sufficiently low sputtering rate and varying experimental conditions. Apparently, the onset of nucleation took place during the first 5 minutes of deposition, followed by a further growth of stable islands known as quantum dots, with the measured radii comparable to the predicted values. Other measurement results confirmed the existence of these dots, including the bandgap energy ∼ 1.80 eV from PL and a 2% at. silicon from EDX and possible amorphous from XRD. The nucleation parameters were predicted as follows: Free energy change per unit volume ∆Gv = 2.64x104 Jmol-1; Surface energies per unit area, γLN = 1.48 Jm-2, γNS = 20.0 - 90.0 Jm-2 and γLS = 0.42 x 10-2 Jm-2; Critical energies ∆G* = 7.53x10-17 - 8.31x10-14 J; Critical radii r* = 9.0- 97.0 nm. This experimental evidence strongly support the early stage growth model of silicon quantum dot deposited on corning glass substrate